Cytotoxic Potential of Flavonoid from Nicotiana tabacum Leaves on MCF-7 Human Breast Cancer Cells - Kusumawardani, Banun; Febi, Qonita Nafilah; Rosidah, Malihatul; Azis, Deri Abdul; Puspitasari, Endah; Nugraha, Ari Satia (Indonesian Society for Cancer Chemoprevention, 2020)
Flavonoid has potential bioactivity as anticancer agents. The flavonoid of cultivated tobacco (Nicotiana tabacum), locally known as “Kasturi”, leaves was screened for its cytotoxicity against MCF-7 human breast cancer cells and non-transformed Vero cells (African normal cell kidney line) in different concentrations. This study aimed to examine the cytotoxic potential of the flavonoid of Kasturi tobacco leaves against MCF-7 human breast cancer cells. Flavonoid obtained from methanolic extracts of Kasturi tobacco leaves, which have been purified from nicotine. The flavonoid of Kasturi tobacco leaves with concentrations of 20 to 640 μg/mL were exposed to MCF-7 and Vero cells for 24 h. Cell viability was evaluated by 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay. Flavonoid of Kasturi tobacco leaves with concentrations of 160 μg/mL decreased the MCF-7 cell viability more than 50%, with an inhibitory concentration 50 (IC50) value of 148.41 μg/mL. Meanwhile, it inhibited 50% of Vero cell viability at 255.35 μg/mL. The flavonoid of Kasturi tobacco leaves has cytotoxic activity on MCF-7 cells, and might be a potential alternative agent for human breast cancer therapy.Keywords: flavonoid, tobacco leaves, human breast cancer cells, anticancer activity